2020
DOI: 10.30994/sjik.v9i2.471
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Habit is Associated With Dysmenorrhea Among Adolescent

Abstract: Dysmenorrhea is pain during menstruation which is felt in the lower abdomen and back. The high incidence of dysmenorrhea in adolescents still does not get enough concern, even though it can cause a person to become weak, pale, reduce concentration, disturb daily activities,  having a negative impact on quality of life. One of the factors that can cause dysmenorrhea is poor dietary habit. This study aims to analyze the correlation between dietary habit and dysmenorrhea in female adolescents. This type of resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The study also found that females who don't eat up breakfast expressively more experiencing dysmenorrhea, when contrasted with females who eat up breakfast and a high admission of fiber diet [30].…”
Section: Acknowledgementmentioning
confidence: 73%
“…The study also found that females who don't eat up breakfast expressively more experiencing dysmenorrhea, when contrasted with females who eat up breakfast and a high admission of fiber diet [30].…”
Section: Acknowledgementmentioning
confidence: 73%
“…Additionally, dietary supplements like omega-3 fatty acids and vitamin B6 may offer relief. Non-pharmacological interventions, including heat therapy and acupuncture, have shown efficacy in alleviating pain [ 5 , 68 70 ]. Furthermore, over-the-counter pain relievers, such as nonsteroidal anti-inflammatory drugs (NSAIDs), can provide effective symptomatic relief.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that regular physical activity and eating breakfast habitually might ease dysmenorrhea; hence, disseminating such information would be helpful. Additionally, previous research has reported that caffeine consumption, consuming spicy or high-fat food, poor sleeping quality, obesity, and exposure to high levels of stress and anxiety might increase dysmenorrhea levels [ 8 , 45 , 50 , 59 ], which should also be conveyed to adolescent girls and their families. Such health education messages need to be reinforced on multiple socio-ecological levels, notably in schools and health institutions, where all can be targeted, regardless of whether they seek health care through primary or secondary prevention [ 57 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%